Cyclists' Behaviour: identification of factors on commuting by bicycle - Andrade, Kátia; Kagaya, Seiichi (Paranoá, 2013)
In Japan, cycling is a widely accepted transportation mode and often used for commuting or other purposes. Accordingly, this paper focuses on the reasons that motivate people to cycle, even though the Japanese transportation policies towards cycling are somewhat limited when compared to other countries with high cycling levels. Behavioural and statistical analyses are presented with a focus on unimodal commuting trips. In the behavioural analysis, commuters’ views on cycling are presented. In the statistical analysis, Nested Logit models are estimated to assess factors with strong influence on cycling. This paper contributes to further understanding the behaviour of active cyclists.